Synthesis of Micron-sized Hexagonal and Flower-like Nanostructures of Lead Oxide (PbO2) by Anodic Oxidation of Lead - Singh, Dinesh Pratap; Srivastava, Onkar Nath (Nano-Micro Letters, 2011)
Micron sized hexagon- and flower-like nanostructures of lead oxide (α-PbO2) have been synthesized by very simple and cost effective route of anodic oxidation of lead sheet. These structures were easily obtained by the simple variation of applied voltage from 2–6 V between the electrodes. Lead sheet was used as an anode and platinum sheet served as a cathode. Anodic oxidation at 2 V resulted in the variable edge sized (1–2 μm) hexagon-like structures in the electrolyte. When the applied potential was increased to 4 V a structure of distorted hexagons consisting of some flower-like structures were obtained. Further increment of potential up to 6 V resulted in flower like structures of α-PbO2 having six petals. The diameter of the flower-like structures was ∼200–500 nm and the size of a petal was ∼100–200 nm.